Conversion Total Knee Arthroplasty. Issue 9 (September 2021) - Ramamurti, Pradip; Fassihi, Safa C.; Stake, Seth; Stadecker, Monica; Whiting, Zachariah; Thakkar, Savyasachi C.
Abstract : Conversion total knee arthroplasty (TKA) represents a heterogeneous group of procedures and most commonly includes TKA performed after ligamentous reconstruction, periarticular open reduction and internal fixation (ORIF), high tibial osteotomy (HTO), and unicompartmental knee arthroplasty (UKA). Relative to patients undergoing primary TKA, patients undergoing conversion TKA often have longer operative times and higher surgical complexity, which may translate into higher postoperative complication rates. There is mixed evidence on implant survivorship and patient-reported outcome measures when comparing conversion TKA and primary TKA, with some studies noting no differences between the procedures and others finding decreased survivorship and outcome scores for conversion TKA. By gaining an improved understanding of the unique challenges facing patients undergoing conversion TKA, clinicians may better set patient expectations, make intraoperative adjustments, and guide postoperative care.